10% Efficient Solar‐to‐Hydrogen Conversion via Ternary‐Phase Organic Light Absorbers With Ni Heazlewoodite Electrocatalysts - Jaemin Park; Jin Hyeong Rhee; Youngeun Kim; Min Jae Kim; Junbeom Park; Sunil V. Barma; Jun Ho Seok; Sang Uck Lee; Eul‐Yong Shin; Dong Su Kim; Hyung Koun Cho; Jin Young Kim; et al. (Carbon Energy)
ABSTRACT The realization of practical solar hydrogen production relies on the development of efficient devices with nontoxic and low‐cost materials. Since the predominant contributors for the performance and cost are the catalyst and the light absorber, it is imperative to develop cost‐effective catalysts and absorbers that are compatible with each other for achieving high performance. In this study, a 10% efficient solar‐to‐hydrogen conversion device was developed through the meticulous integration of low‐cost Ni Heazlewoodite‐based catalysts for the hydrogen evolution reaction (HER) and ternary bulk heterojunction organic semiconductor (OS)‐based light absorbers. Se‐incorporated Ni3S2 was synthesized using a simple one‐step hydrothermal method, which demonstrated a low overpotential and Tafel slope, indicating superior HER activity compared to Ni₃S₂. The theoretical calculation results validate the enhanced HER performance of the Se‐incorporated Ni₃S₂ catalyst in alkaline electrolytes. The ternary phase organic light absorber is designed to generate tailored photovoltage and maximized photocurrent, resulting in a photocurrent density of 8.24 mA cm−2 under unbiased conditions, which corresponds to 10% solar to hydrogen conversion. Low‐temperature photoluminescence spectroscopy results revealed that the enhanced photocurrent density originates from a reduction in both phonon‐ and vibration‐induced inter‐ and intramolecular non‐radiative decay. Our results establish a new benchmark for the emerging OS‐based efficient solar hydrogen production based on nontoxic and cost‐effective materials.